Presença de Ureaplasma diversum em vacas de leite pertencentes a municípios do Norte de Mato Grosso, Brasil - Azevedo, Jaqueline Bruning (2016)
Ureaplasma diversum infection in bovine females may result in various reproductive problems, including granular vulvovaginitis, abortion, weak calves, salpingitis and spontaneous abortion. The presence of U. diversum in a dairy bovine population from midwestern Brazil has not been established. The aim of this study was to determine whether U. diversum was present in dairy cattle from midwestern Brazil using polymerase chain reaction (PCR). Vulvovaginal mucus was analyzed from 203 animals located in six municipalities in the north region of Mato Grosso State, Brazil. A total of 25% of dairy cows with vulvovaginitis were positive for U. diversum. The factors evaluated were included in a multivariable logistic regression model with the presence of at least one positive animal in the herd serving as the dependent variable. Three variables were significantly associated with a U. diversum positive PCR and were included in the final multivariable model: number of deliveries, vulvar lesions and reproductive problems. For each new delivery, the chance of U. diversum infection decreased 0.03-fold, indicating that cows with the highest number of deliveries were more protected. The presence of vulvar lesions was increased 17.6-fold in females positive for U. diversum, suggesting that this bacteria could be related to the red granulate lesions in the vulvar mucosa, whereas reproductive problems were increased 7.6-fold. However, further investigations should be conducted to ascertain the effects of U. diversum in association with other mycoplasma species in the herds studied.